2012
DOI: 10.1002/dvdy.23742
|View full text |Cite
|
Sign up to set email alerts
|

Developmental expression ofDrosophilaWiskott‐Aldrich Syndrome family proteins

Abstract: Background Wiskott-Aldrich Syndrome (WASP) family proteins participate in many cellular processes involving rearrangements of the actin cytoskeleton. To the date, four WASP subfamily members have been described in Drosophila: Wash, WASp, SCAR, and Whamy. Wash, WASp, and SCAR are essential during early Drosophila development where they function in orchestrating cytoplasmic events including membrane-cytoskeleton interactions. A mutant for Whamy has not yet been reported. Results We generated monoclonal antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 75 publications
7
35
3
Order By: Relevance
“…Thus, we generated WASH conditional knockout mice (23) in order to determine the role of WASH in thymocyte development and peripheral T cell function. We found that total WASH knockout results in embryonic lethality around day E7.5 (T. S. Gomez and D. D. Billadeau, data not shown), which is consistent with studies in Drosophila, which have shown that WASH is expressed throughout embryogenesis and that WASH KO Drosophila are not viable (13,31). Therefore, we crossed WASH flox/ϩ mice with CD4 Cre mice to generate CD4 Cre WASH flox/flox conditional knockout (WASHout) mice, which allows for specific Cre-mediated excision of WASH in T cells in late thymic development (32).…”
Section: Cd4supporting
confidence: 90%
“…Thus, we generated WASH conditional knockout mice (23) in order to determine the role of WASH in thymocyte development and peripheral T cell function. We found that total WASH knockout results in embryonic lethality around day E7.5 (T. S. Gomez and D. D. Billadeau, data not shown), which is consistent with studies in Drosophila, which have shown that WASH is expressed throughout embryogenesis and that WASH KO Drosophila are not viable (13,31). Therefore, we crossed WASH flox/ϩ mice with CD4 Cre mice to generate CD4 Cre WASH flox/flox conditional knockout (WASHout) mice, which allows for specific Cre-mediated excision of WASH in T cells in late thymic development (32).…”
Section: Cd4supporting
confidence: 90%
“…Thus, redundant or compensatory pathways might mask WASH function in developing eggs. Previous expression data in wild-type flies revealed an accumulation at the oocyte cortex in addition to an overall cytoplasmic expression in all nurse and somatic follicle cells throughout oogenesis (Rodriguez-Mesa et al, 2012). The protein-Aaffinity-purified monoclonal antibody (mAb P3H3; Rodriguez-Mesa et al, 2012) used in this study specifically recognizes WASH in immunoblots (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…The Arp2/3 complex was purchased from Cytoskeleton, Inc. Coprecipitation assays with GST-tagged proteins were conducted as described previously (16). Pellets and supernatants were denatured in Laemmli sample buffer and fractionated by SDS/PAGE, followed by immunoblotting with α-WASp antibody P5E1 (41).…”
Section: Methodsmentioning
confidence: 99%